169PM-phase phosphoprotein 8 promotes gastric cancer growth and metastasis via p53/Bcl-2 and EMT-related signalling pathways. (24th November 2019) - Wang, Y; Wang, C; Xiao, H; Wu, H; He, H; Cui, J; Li, W
Abstract: Background: The main issue of this study is to demonstrate whether M-phase phosphoprotein 8 (MPP8) affect gastric tumour growth and metastasis. Methods: Retrospective study was proceeded in 280 patients' surgical specimens with different disease stages. Lentivirus delivery of short hairpin RNA targeting MPP8 was also used to explore the function of MPP8 in gastric cancer cells. Quantitative real-time PCR and western blot were applied to measure apoptosis and metastasis relative biomarker. Results: The present study revealed that MPP8 expression was higher in surgical specimens from patients with gastric cancer (vs. normal adjacent tissues), and that elevated expression was associated with male sex (vs. female sex), intermediate differentiation (vs. poorly differentiated cancer), and later stage (vs. earlier stage). Furthermore, MPP8 overexpression in tumour tissues was marginally associated with a poor prognosis, with a significant relationship between MPP8 overexpression and prognosis among patients with poorly differentiated gastric cancer. Inhibition of MPP8 in these cells significantly suppressed proliferation and colony formation, promoted apoptosis, and repressed invasion. Furthermore, silencing of MPP8 remarkably increased the expression of apoptosis-related proteins (p53, Bax, and PARP), and down-regulated Bcl-2 expression. Silencing of MPP8 also decreased the expression of metastasis pathway-related proteins (N-cadherin and vimentin), and as well as the levels of anti-oncogene ZEB1, MET, and KRAS mRNA. Conclusions: These results suggest that MPP8 plays a critical role in regulating gastric cancer apoptosis and metastasis via the p53/Bcl-2 and EMT-related signalling pathways, respectively, which may indicate that MPP8 is a promising target for treating gastric cancer. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.